SKEW- SEMI DERIVATION ON SEMI-PRIME RINGS - Shivani Parashar; Sanjay Chaudhary; Shyamli Gupta (Utilitas Mathematica, 2025)
For this study, Π represents a semi-prime ring and we introduce a new class of derivations that generalizes skew derivation and semi - derivation, we call it “ skew-semi derivation”. By assuming that Ώ is a skew-semi derivation with an automorphism α:Π→Π associated with it. In this paper, we prove some results on skew - semi derivation for semi-prime ring.